2010
DOI: 10.1016/j.chb.2010.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Motivational factors that influence the acceptance of Moodle using TAM

Abstract: a b s t r a c tMoodle and other virtual teaching platforms have bolstered the ability and motivation of universities to support distance learning.The aim of our study is to improve understanding of the motivational factors behind student satisfaction, or dissatisfaction, with the Web-based learning platform, Moodle.Our study extends the Technology Acceptance Model (TAM) to include technical support and perceived self-efficacy, with the expectation that they influence usage of Moodle. We surveyed 226 students o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
232
4
30

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 432 publications
(296 citation statements)
references
References 49 publications
30
232
4
30
Order By: Relevance
“…Theoretically, TAM is based on Fishbein and Ajzen's Theory of Reasoned Action (1975) and emphasizes users' beliefs, attitudes and intentions in adopting technology (Sánchez and Hueros, 2010). TAM has been widely used in a variety of studies using a range of variables and it has consistently been found to be strong predictors of acceptance behavior (Shipps and Phillips, 2013;Bagozzi 2007).…”
Section: Technology Acceptance Model (Tam)mentioning
confidence: 99%
“…Theoretically, TAM is based on Fishbein and Ajzen's Theory of Reasoned Action (1975) and emphasizes users' beliefs, attitudes and intentions in adopting technology (Sánchez and Hueros, 2010). TAM has been widely used in a variety of studies using a range of variables and it has consistently been found to be strong predictors of acceptance behavior (Shipps and Phillips, 2013;Bagozzi 2007).…”
Section: Technology Acceptance Model (Tam)mentioning
confidence: 99%
“…El soporte técnico se refiere a las personas capacitadas para ayudar a los usuarios en la solución de problemas relacionados con el hardware y software de computadora, para lo cual se valen de múltiples opciones que les permite interactuar de forma directa (Arteaga & Duarte, 2010).…”
Section: Soporte Técnicounclassified
“…Lo expuesto coincide con los resultados de varios estudios (AlQudah Ahmed, 2014;Arteaga & Duarte, 2010;Ngai, Poon & Chan, 2007;Ramirez-Anormaliza, Sabaté & Guevara-Viejo, 2015). Esto motivó la inclusión de este constructo en la presente investigación.…”
Section: Soporte Técnicounclassified
“…Az utóbbi időben azonban egyre nagyobb népszerűségnek örvend az oktatási kutatások területén is (Leguina [2015]). Alkalmazzák például a tanulói vagy oktatói attitűd, a megítélés, a képesség vagy a szándék vizsgálatára (Ahmad et al [2010], Al-Gahtani [2016], Cheng [2013], De Smet et al [2012], Del Barrio-Romero-Frías-Arquero [2013], Najmul Islam [2013], Lee-Hsiao-Purnomo [2014], Sanchez-Franco [2010], Sánchez-Hueros [2010], van Raaij-Schepers [2008], Yang et al [2011]). …”
Section: Tárgyszóunclassified